Analysis of the Role of Women's Movement in Overcoming Female Genital Mutilation in Order to Promote Change in Africa - Reditania, Zilda Clarita; Fitriyah, Fitriyah; Alfirdaus, Laila Kholid (Journal La Sociale, 2025)
This study discusses the role of women's movements in addressing the practice of Female Genital Mutilation (FGM), which is considered a violation of Human Rights. FGM is inflicted on women based on cultural demands, effectively stripping women of control over their own bodies. Female Genital Mutilation (FGM) is recognized as a form of human rights abuse that reflects deep gender inequality and constitutes extreme discrimination against girls and women. The research is conducted qualitatively, with data collection carried out through journals, books, websites, and scientific reports. In this study, the author concludes that the women's movement in the fight against FGM is effectively implemented due to the commitment of the Desert Flower Foundation and its supporters, which stands as a powerful and exemplary example of hope, courage, and solidarity. The efforts to end FGM in Africa over the years have garnered attention as international, regional, and national actors have united in taking actions designed to address this harmful practice. As the struggle against FGM continues, the Desert Flower Foundation remains a key player in the global effort to enable women to live dignified and free lives.